Occupational stress and associated factors among general practitioners in China: a national cross-sectional study - Jing Feng; Heng Jiang; Xin Shen; Zihui Lei; Liqing Li; Yi Zhu; Mingye Zhang; Tingting Yang; Xin Meng; Hongkun Di; Wenqi Xia; Zuxun Lu; et al. (BMC Public Health, 2022)
Abstract Background Occupational stress among general practitioners (GPs) is a public health concern. This study aimed to investigate the prevalence and factors associated with occupational stress among GPs in China. Methods A cross-sectional design was used. Data were collected from 3,236 GPs in eastern, central, and western China (response rate, 99.75%) between October 2017 and February 2018 using a structured self-administered questionnaire. An ordinal logistic regression model was used to identify the factors associated with occupational stress among GPs. Results Among these respondents, 313 (9.67%), 1,028 (31.77%), and 1,895 (58.56%) of GPs had a low, medium, and high level of occupational stress, respectively. GPs from central China, with temporary work contracts, without management responsibility, receiving a moderate level of income, and with moderate occupational development opportunities had a lower level of occupational stress. GPs with greater than 40 working hours per week and those who worked overtime occasionally or frequently had a higher level of occupational stress. Conclusions The prevalence of occupational stress among GPs is high in China. Substantial regional variation in determinants of occupational stress among GPs was observed. These findings should inform the design of policies to reduce the occupational stress of GPs.